The catholic just war tradition and russia's war against Ukraine - Лутц, Д. (Київський національний університет імені Тараса Шевченка, 2023)
The Catholic just war tradition is rooted in the philosophy of Cicero and has been developed by subsequent philosophers and theologians up to the present day. A war can be just only if its purpose is to restore the peace. Applying the just war criteria to the Russian Federation's invasion of the sovereign nation of Ukraine on 24 February 2022 yields the conclusion that it is an unjust war of aggression and that Ukraine is justified in defending itself militarily. Although Pope Francis appealed to all parties to avoid violence, that did not prevent the outbreak of war. After this major escalation of the war that began with Russia's unlawful annexation of Crimea in 2014, both Pope Francis and the President of the Pontifical Council for Promoting Christian Unity criticized Russian Orthodox Patriarch Kirill for supporting Russia's invasion. It is unclear where Pope Francis stands regarding the possibility of a just war. He has made statements that appear to reject the just war tradition as obsolete today. At the same time, he has recognized the right of Ukrainians to defend their country. It is not unjust for Ukrainian soldiers to pay the ultimate sacrifice in defense of their homeland. The profession of arms is a noble vocation. Thomas Aquinas recognized the virtues of military heroes who defend the common good in a just war. Many Ukrainian soldiers have performed acts of heroic virtue. Ukrainian Catholic University Vice Rector Myroslav Marynovych met with Pope Francis in June 2022 and reported that the Roman Pontiff is open to reconsidering the question of justice in warfare. In clarifying the concept of just war, it is important to point out that a war can be unjust on both sides, or just on one side and unjust on the other, but not just on both sides. Consequently, war is always unjust in the sense that all wars are unjust on at least one side. That does not mean, however, that it is impossible for a war to be just on one of its sides.

Католицька традиція справедливої війни сягає корінням у філософію Цицерона і розвивається наступними філософами та бого- словами аж до наших днів. Війна може бути справедливою лише тоді, коли її метою є відновлення миру. Застосування критеріїв справедливої війни до вторгнення Російської Федерації в суверенну державу Україна 24 лютого 2022 року дає змогу зробити висновок, що це несправедлива агресивна війна і що Україна має право захищати себе військовим шляхом. Хоча Папа Франциск звернувся до всіх сторін із закликом уникати насильства, це не допомогло запобігти початку війни. Після цієї великої ескалації війни, яка почалася з незаконної анексії Криму Росією в 2014 р., і Папа Франциск, і президент Папської ради сприяння єдності християн розкритикували російського православного патріарха Кирила за підтримку російського вторгнення. Незрозуміло, яку позицію займає Папа Франциск щодо можливості справедливої війни. Він зробив заяви, які, здається, відкидають традицію справедливої війни як застарілу на сьогодні. Водночас, він визнав право українців захищати свою країну. Для українських солдатів не є несправедливим платити найвищу жертву, захищаючи свою батьківщину. Професія зброяра – це благородне покликання. Тома Аквінський визнавав чесноти військових героїв, які захищають спільне благо у справедливій війні. Багато українських воїнів здійснили акти героїчної чесноти. Віце-ректор Українського католицького університету Мирослав Маринович у червні 2022 року зустрівся з Папою Франциском і повідомив, що Римський понтифік відкритий до переосмислення питання справедливості у війні. З'ясовуючи поняття справедливої війни, важливо зазначити, що війна може бути несправедливою з обох сторін, або тільки з одного боку і несправедливою з іншого, але не тільки з обох сторін. Отже, війна завжди несправедлива в тому сенсі, що всі війни несправедливі принаймні з одного боку. Це, однак, не означає, що війна не може бути справедливою для однієї зі сторін.
Католицька традиція справедливої війни і війна росії проти України
Keywords: just war; jus ad bellum; jus in bello; jus post bello; virtues; peace; справедлива війна; jus ad bellum; jus in bello; jus post bello; чесноти; мир